Iraqi Stock Exchange Reactions to the Oil price, Covid-19 Aftermath, and the Saudi Stock Exchange Movements pre-during Vaccination Program - Asaad, Zeravan Abdulmuhsen; Al-Delawi, Amjad Saber (International Journal of Energy Economics and Policy, 2022)
The study attempts to understand the influence of Brent oil price per barrel (BOP), the general index of 30 stocks in Saudi Arabia (MSCI30), the number of Covid-19 new infected cases (NIC_19), ounce gold price (OGP), and US dollar base to Iraqi Dinar exchange rate (USD_IQD) upon Iraq stock exchange (ISX60) using the daily period (25 February 2020 to 15 July 2021) divided into three subperiod; whole period pre-during covid-19, pre-Covid-19 and during Covid-19 vaccination process. The results indicate the long-run relationship between the regressors and the Iraq stock exchange in the subperiod before Covid-19 and during the Covid-19 vaccination process but did not appear for the whole period pre-during the covid-19 vaccination process. The results reveal a positive influence of (MSCI30 and USD_IQD) on ISX60 in the long term for a period before the Covid-19 vaccination process. And, the results indicate a negative influence of (BOP and OGP) respectively on (ISX60) in the long term, and (MSCI30) positively leads ISX60 in the long term during the Covid-19 vaccination process. The results are crucial to governments, investors, and policymakers because the Iraqi economic movements and stock exchange development need more highlight in the further studies, especially the vaccine discovery consequences.